A large observational data study supporting the PROsPeR score classification in poor ovarian responders according to live birth outcome. Issue 6 (16th April 2021) - Lehert, P; Arvis, P; Avril, C; Massin, N; Parinaud, J; Porcu, G; Rongières, C; Sagot, P; Wainer, R; D'Hooghe, T
Abstract: STUDY QUESTION: Can the Poor Responder Outcome Prediction (PROsPeR) score identify live birth outcomes in subpopulations of patients with poor ovarian response (POR) defined according to the ESHRE Bologna criteria (female age, anti-Müllerian hormone (AMH), number of oocytes retrieved during the previous cycle (PNO) after treatment with originator recombinant human follitropin alfa? SUMMARY ANSWER: The PROsPeR score discriminated the probability of live birth in patients with POR using observational data with fair discrimination (AUC ≅ 70%) and calibration, and the AUC losing less than 5% precision compared with a model developed using the observational data. WHAT IS KNOWN ALREADY: Although scoring systems for the likelihood of live birth after ART have been developed, their accuracy may be insufficient, as they have generally been developed in the general population with infertility and were not validated for patients with POR. The PROsPeR score was developed using data from the follitropin alfa (GONAL-f; Merck KGaA, Darmstadt, Germany) arm of the Efficacy and Safety of Pergoveris in Assisted Reproductive Technology (ESPART) randomized controlled trial (RCT) and classifies women with POR as mild, moderate or severe, based upon three variables: female age, serum AMH level and number of oocytes retrieved during the previous cycle (PNO). STUDY DESIGN, SIZE, DURATION: The external validation of the PROsPeR score was completed using data derived from eight different centres in France. In addition, the follitropin alfa data from the ESPART RCT, originally used to develop the PROsPeR score, were used as reference cohort. The external validation of the PROsPeR score l was assessed using AUC. A predetermined non-inferiority limit of 0.10 compared with a reference sample and calibration (Hosmer–Lemeshow test) were the two conditions required for evaluation. PARTICIPANTS/MATERIALS, SETTING, METHODS: The observational cohort included data from 8085 ART treatment cycles performed with follitropin alfa in patients with POR defined according to the ESHRE Bologna criteria (17.6% of the initial data set). The ESPART cohort included 477 ART treatment cycles with ovarian stimulation performed with follitropin alfa in patients with POR. MAIN RESULTS AND THE ROLE OF CHANCE: The external validation of the PROsPeR score to identify subpopulations of women with POR with different live birth outcomes was shown in the observational cohort (AUC = 0.688; 95% CI: 0.662, 0.714) compared with the ESPART cohort (AUC = 0.695; 95% CI: 0.623, 0.767). The AUC difference was −0.0074 (95% CI: −0.083, 0.0689). This provided evidence, with 97.5% one-sided confidence, that there was a maximum estimated loss of 8.4% in discrimination between the observational cohort and the ESPART cohort, which was below the predetermined margin of 10%. The Hosmer–Lemeshow test did not reject the calibration when comparing observed and predicted data (Hosmer–Lemeshow test = 1.266688; P = 0.260). LIMITATIONS, REASONS FOR CAUTION: The study was based on secondary use of data that had not been collected specifically for the analysis reported here and the number of characteristics used to classify women with POR was limited to the available data. The data were from a limited number of ART centres in a single country, which may present a bias risk; however, baseline patient data were similar to other POR studies. WIDER IMPLICATIONS OF THE FINDINGS: This evaluation of the PROsPeR score using observational data supports the notion that the likelihood of live birth may be calculated with reasonable precision using three readily available pieces of data (female age, serum AMH and PNO). The PROsPeR score has potential to be used to discriminate expected probability of live birth according to the degree of POR (mild, moderate, severe) after treatment with follitropin alfa, enabling comparison of performance at one centre over time and the comparison between centres. STUDY FUNDING/COMPETING INTEREST(S): This analysis was funded by Merck KGaA, Darmstadt, Germany. P.L. received grants from Merck KGaA, outside of the submitted work. N.M. reports grants, personal fees and non-financial support from Merck KGaA outside the submitted work. T.D.H. is Vice President and Head of Global Medical Affairs Fertility, Research and Development at Merck KGaA, Darmstadt, Germany. P.A. has received personal fees from Merck KGaA, Darmstadt, Germany, outside the submitted work. C.R. has received grants and personal fees from Gedeon Richter and Merck Serono S.A.S., France, an affiliate of Merck KGaA, Darmstadt, Germany, outside the submitted work. P.S. reports congress support from Merck Serono S.A.S., France (an affiliate of Merck KGaA, Darmstadt, Germany), Gedeon Richter, TEVA and MDS outside the submitted work. C.A., J.P., G.P. and R.W. declare no conflict of interest. TRIAL REGISTRATION NUMBER: N/A